Dialectic of Identity: Paskvalić’s Guide to Four Poems Dedicated to Serenissima - Ferri, Ane (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
This paper comprehensively explores the national-literacy identity of the Renaissance poet Ludovik Paskvalić, through a study of four of his poems, in which the poet’s close relationship with the Republic of Venice is reflected. Despite the note about his identity that the poet himself left on the cover of his printed Italian songbook entitled Rime volgari, the scientific and professional public often placed Paskvalić in different, often inaccurate, identity frameworks. The reasons for the poet’s inclusion in the corpus of Italian or Venetian Renaissance poets can be found in Paskvalić’s prominent Italianist activity, in his linguistic virtuosity in the Italian language, which was not his native language, as well as in the fact that until today the scientific public has not managed to find Paskvalić’s literary legacy in his mother tongue. Thus, the Renaissance poet from the Bay of Kotor first found his place in Italian and world anthologies, and many years later in scientific studies from this side of the Adriatic Sea. Wrong premises regarding the poet’s national identity often had a negative impact on the analysis of his verses. The aim of this paper is to use the example of four of Paskvalić’s poems dedicated to the Republic of St. Marco from his collection in the Italian language, the occasions and contexts in which the poems were written are analyzed to shed light on the poet’s identity through the explanation of his attitude of full respect and admiration towards Serenissima. The method is of a comparative, research and literary-historical character, based on combinatorial research about the author, through the analysis of four of his poems dedicated to the capital of the Republic of Venice. In this way, for the first time, attention would be paid to the analysis of the opening and closing songs of the second part of the Italian songbook, completely excluded from the significantly larger number of other songs from the same collection that have been analyzed in detail so far according to their stylistic and typological characteristics. Our research strongly supports the claim that the writer’s national identity should be based on an understanding of the wider context of the time and space in which he created, as well as his own determination, which can be read from his work, but also from other testimonies.